SLOPE STABILITY ANALYSIS ON THE FINAL PIT DESIGN OF PRIMARY TIN MINE AT PT XYZ IN BANGKA BELITUNG PROVINCE USING FINITE ELEMENT METHOD - Abdillah Desrian, Gianluca
PT XYZ is a primary tin mine in Bangka Belitung Province which has a plan to open two new pits called Pit Block 1 and Pit Block 3. The new Pit mine design has been made. To ensure that the value of the safety factor for overall slope is greater than 1.5, slope stability analysis must be carried out on the mine design that has been made. Slope stability analysis is carried out using the finite element method by the help of Rocscience Phase2 8.0 software. In the finite element method, slope safety factors are approached by the form of strength reduction factor (SRF) which the shear strength parameters are gradually reduced, so that all elements in the slope collapsed. The slopes analyzed are taken from the selected vertical section, then modeled according to the modeling rules using the finite element method. The simulation results show that from the 17 slopes analyzed in Pit Block 1 and Pit Block 3, there are 6 slopes that have SRF values above 1.5, while the other 11 slopes have SRF values below 1.5. In Block 1, the angle of overall slope of cross section 1 on left side, cross section 2 on both sides, and cross section 3 on both sides are changed to be 15o. Overall slope of section 1 on the right side and section 4 on both sides are changed to be 20o. Displacement in the crest has a value between 0.15 and 0.92 m, while at the toe is ranged between 0.09 and 0.2 m. The slope on Block 1 has a height of 87.4 m-97.4 m. In Block 3, the angle of overall slope cross section 1 on the left side, cross section 2 on the right side, and cross section 4 on the left side are changed to be 15o. The angle of cross section 3 on the right side is changed to be 20o. The angle of overall slope of cross section 1 on the left side, cross section 2 on the left side, and cross section 4 on the right side are changed to be 25o. The angle of cross section 3 on the left side is changed to be 30o. Displacement in the crest has a value between 0.07 and 1.04 m, while at the toe is ranged between 0.01 and 0.12 m. The slope of Block 3 has a height of 49.9 m-72.3 m.